إكراه المتهم على الاعتراف في القانون الأفغاني من منظور الشريعة الإسلامية: Coercion of the Accused to Confess in Afghan Law from the Perspective of Islamic Sharia - Ahmad Nesar, Muneer; Laeba, Muhammad; Ibrahim Negasi, Mohamed (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2025)
ملخص البحث يتناول البحث قضية إكراه المتهم على الاعتراف في القانون الأفغاني ومدى توافقه مع أحكام الشريعة الإسلامية والمعايير الدولية لحقوق الإنسان، في ظل التحديات القانونية والواقعية. يهدف إلى تحليل موقف الشريعة الإسلامية والقانون الأفغاني من الاعترافات القسرية، وتقييم مدى انسجام التشريعات الأفغانية مع المبادئ الإسلامية والمواثيق الحقوقية الدولية. ويعتمد البحث على المنهج التحليلي المقارن، من خلال دراسة النصوص القانونية والشرعية وتحليل التطبيقات العملية لهذه الأحكام في النظام القانوني الأفغاني. وتكمن أهميته في تسليط الضوء على ضمانات العدالة الجنائية في أفغانستان، وتعزيز حماية حقوق المتهمين، مع تقديم توصيات تساهم في تطوير النظام القانوني بما يحقق العدالة وفقًا للمبادئ الإسلامية والمعايير الدولية. ABSTRACT The study examines the issue of coercing the accused to confess in Afghan law and its compatibility with the principles of Islamic Sharia and international human rights standards, considering the legal and practical challenges. It aims to analyze the stance of Islamic Sharia and Afghan law on forced confessions and assess the extent to which Afghan legislation aligns with Islamic principles and international human rights conventions. The research adopts a comparative analytical methodology by examining legal and Sharia texts and analyzing the practical applications of these provisions within the Afghan legal system. Its significance lies in highlighting the guarantees of criminal justice in Afghanistan, strengthening the protection of defendants’ rights, and providing recommendations that contribute to the development of the legal system to ensure justice in accordance with Islamic principles and international standards.